Is It Possible to Predict the Future in First-Episode Psychosis? - Suvisaari, Jaana; Mantere, Outi; Keinänen, Jaakko; Mäntylä, Teemu; Rikandi, Eva; Lindgren, Maija; Kieseppä, Tuula; Raij, Tuukka T. (Frontiers in Psychiatry, 2018)
The outcome of first-episode psychosis (FEP) is highly variable, ranging from early sustained recovery to antipsychotic treatment resistance from the onset of illness. For clinicians, a possibility to predict patient outcomes would be highly valuable for the selection of antipsychotic treatment and in tailoring psychosocial treatments and psychoeducation. This selective review summarizes current knowledge of prognostic markers in FEP. We sought potential outcome predictors from clinical and sociodemographic factors, cognition, brain imaging, genetics and blood-based biomarkers, and we considered different outcomes, like remission, recovery, physical comorbidities and suicide risk. Based on the review, it is currently possible to predict the future for FEP patients to some extent. Some clinical features ‒ like the longer duration of untreated psychosis, poor premorbid adjustment, the insidious mode of onset, the greater severity of negative symptoms, comorbid substance use disorders, a history of suicide attempts and suicidal ideation and having non-affective psychosis ‒ are associated with a worse outcome. Of the social and demographic factors, male gender, social disadvantage, neighbourhood deprivation, dysfunctional family environment and ethnicity may be relevant. Treatment non-adherence is a substantial risk factor for relapse, but a small minority of patients with acute onset of FEP and early remission may benefit from antipsychotic discontinuation. Cognitive functioning is associated with functional outcomes. Brain imaging currently has limited utility as an outcome predictor, but this may change with methodological advancements. Polygenic risk scores might be useful as one component of a predictive tool, and pharmacogenetic testing is already available and valuable for patients who have problems in treatment response or with side effects. Most blood-based biomarkers need further validation. None of the currently available predictive markers has adequate sensitivity or specificity used alone. However, personalized treatment of FEP will need predictive tools. We discuss some methodologies, such as machine learning, and tools that could lead to the improved prediction and clinical utility of different prognostic markers in FEP. Combination of different markers in machine learning models with a user friendly interface, or novel findings from e.g. molecular genetics or neuroimaging, may result in computer-assisted clinical applications in the near future.